1990
DOI: 10.1002/1097-0142(19901001)66:7<1453::aid-cncr2820660703>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Induction chemotherapy with a new regimen alternating cisplatin, fluorouracil with mitomycin, hydroxyurea and bleomycin in carcinomas of nasopharynx or other sites of the head and neck region

Abstract: Sixty-six patients with locally advanced (Stages III and IV) carcinoma of the head and neck were treated with three cycles of induction chemotherapy, consisting of cisplatin, fluorouracil (FU) infusion, bleomycin, mitomycin, and hydroxyurea, followed by radiotherapy and/or surgery. There were 48 men and 18 women with a median age of 55 years (range, 18 to 75 years) and Karnofsky performance status of 80 (range, 40 to 90). Primary site was nasopharynx (28 patients), followed by larynx (12) and others (26). Fort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Compared with studies on adjuvant chemotherapy, Phase II trials regarding induction chemotherapy described better patient tolerance and treatment compliance, as well as a high locoregional response of 72–100% 13, 16–20. Despite these promising results, none of the five randomized trials we studied demonstrated an overall survival advantage for all disease stages with this approach compared with RT alone (Table 2).…”
Section: The Role Of Chemotherapy In Locoregionally Advanced Npc–how mentioning
confidence: 89%
“…Compared with studies on adjuvant chemotherapy, Phase II trials regarding induction chemotherapy described better patient tolerance and treatment compliance, as well as a high locoregional response of 72–100% 13, 16–20. Despite these promising results, none of the five randomized trials we studied demonstrated an overall survival advantage for all disease stages with this approach compared with RT alone (Table 2).…”
Section: The Role Of Chemotherapy In Locoregionally Advanced Npc–how mentioning
confidence: 89%
“…Postradiation or postoperative adjuvant chemotherapy seldom is tried because compromised vasculature, caused by radiation change or ablative surgery, will reduce drug penetration and the effectiveness of chemotherapy. The majority of clinical trials involve either neoadjuvant or concomitant chemotherapy for advanced SCCHN 3–6, 9–45. In general, the disadvantages of neoadjuvant chemotherapy include delayed primary treatment in nonresponders, refusal of further curative therapy in responders, triggering of accelerated repopulation of surviving clonogens,48 and cross‐resistance to further radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…SCCHN refers to a heterogeneous population of patients with a primary tumor arising from the oral cavity, nasopharynx, oropharynx, hypopharynx, larynx, nasal cavity, paranasal sinus, etc. There are substantial discrepancies in terms of treatment outcome between the various anatomic subsites 17, 40, 42. Second, it has been well established that tumor cell heterogeneity exists in fresh tumor biopsies and long term cell culture lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From August 1984 to May 1991, 154 patients with locally advanced HNC were entered in 3 consecutive phase II trials [20][21][22]. Eligibility criteria were the following: histologically confirmed locally advanced non-metastatic (Mo) HNC, measurable or evaluable disease, normal hepatic and renal functions, platelets > 100,00/l, leukocytes >4,000/l, performance status (PS) >40 of Karnofsky's scale, age <75 years, absence of active ischemic heart disease, no prior therapy except a biopsy procedure, and a witnessed informed consent according to our institutional policies.…”
Section: Methodsmentioning
confidence: 99%